CONVENTION REPORT. (The Accounting Review, 1940)
Abstract The twenty-fourth annual convention of the American Accounting Association was held at the Adelphia Hotel, Philadelphia, Pennsylvania on December 28-29, 1939. The president of the association opened the session with the following remarks: "We are assembled in the twenty-fourth annual convention of this group. We have come to the end of our fourth year as the American Accounting Association. It is customary for the president to present to the annual meeting some report of the Association's activity during the year. It is on the record of the year 1939 that I wish to comment briefly." "For the purpose of establishing a background against which to evaluate the current performance, it may be well for you to have some reminder of what has gone before. In December of 1935 at New York, the American Association of University Instructors in Accounting was reconstituted as the American Accounting Association." In the development of accounting research the Association stands ever ready to lend all help within its power. Cooperation with any and all interested individuals or groups or associations is assured. It was the hope of those who were instrumental in changing the character and name of the Association in 1935 that the Association would ultimately become the one organization recognized as most fully representing the study of accounting as a field of learning.